A Fresh Start to a Healthier You! program improves fruit and vegetable consumption and risk of food insecurity: Findings from Texas - Katelin M. Alfaro Hudak; Lindsey Breunig-Rodriguez; Renda J. Nelson; Elizabeth F. Racine (Preventive Medicine Reports, 2025)
Objective: The goal of Supplemental Nutrition Assistance Program Education (SNAP-Ed) is to increase the likelihood that individuals with lower incomes who are eligible for SNAP benefits will choose healthy foods within a limited budget and be physically active. This study aimed to evaluate how participation in a Texas SNAP-Ed program A Fresh Start to a Healthier You! (Fresh Start) was associated with participants' fruit and vegetable consumption, use of food resource management strategies, and risk of food insecurity. Methods: The study used survey data collected February 2021–September 2023 from counties across Texas. This single group pre/post evaluation used generalized linear models to assess changes in outcomes from baseline to program completion. Models adjusted for age, sex, race/ethnicity, and educational attainment. Results: Participants who completed Fresh Start were 18–20 percentage points more likely to utilize food resource management strategies (average marginal effect [AME]: 18.2–20.0, p < 0.0001). The average change in being at risk of food insecurity decreased 3 percentage points (AME: 3.2, p = 0.012) following completion of Fresh Start. Measures of F&V intake significantly increased (AME: 6.7–36.3, p < 0.001), and the average number of days participants engaged in physical activity each week increased by 0.7 (AME: 0.7, p < 0.0001). Participation in Fresh Start was associated with improved food security, greater utilization of food resource management strategies, and increased fruit and vegetable consumption and physical activity. Conclusion: This study supports the use of SNAP-Ed and other nutrition education programs as one avenue to improve food security and diet behavior in households with lower incomes.